Altered microbiota composition reflects enhanced communication in 15q11-13 CNV mice. (December 2020) - Septyaningtrias, Dian Eurike; Lin, Chia-Wen; Ouchida, Rika; Nakai, Nobuhiro; Suda, Wataru; Hattori, Masahira; Morita, Hidetoshi; Honda, Kenya; Tamada, Kota; Takumi, Toru
Highlights: 15q dup mice has less species diversity of gut microbiota. Neomycin treatment improved species richness and USV call number in 15q dup mice. We identified beneficial OTUs/bacteria for USV. Abstract: Autism spectrum disorder (ASD) is a complex and heterogeneous neurodevelopmental disorder. In addition to the core symptoms of ASD, many patients with ASD also show comorbid gut dysbiosis, which may lead to various gastrointestinal (GI) problems. Intriguingly, there is evidence that gut microbiota communicate with the central nervous system to modulate behavioral output through the gut-brain axis. To investigate how the microbiota composition is changed in ASD and to identify which microbes are involved in autistic behaviors, we performed a 16S rRNA gene-based metagenomics analysis in an ASD mouse model. Here, we focused on a model with human 15q11-13 duplication ( 15q dup ), the most frequent chromosomal aberration or copy number variation found in ASD. Species diversity of the microbiome was significantly decreased in 15q dup mice. A combination of antibiotics treatment and behavioral analysis showed that neomycin improved social communication in 15q dup mice. Furthermore, comparison of the microbiota composition of mice treated with different antibiotics enabled us to identify beneficial operational taxonomic units (OTUs) for ultrasonic vocalization.